A Case Report on VT from TV: DVT and PE from Prolonged Television Watching - Alan Lucerna; James Espinosa; Lindsey Ackley; Philip Carhart; Douglas Stranges; Risha Hertz (Case Reports in Pulmonology)
Pulmonary embolus (PE) and deep vein thrombosis are diagnoses that are commonly made in the emergency department. Well known risk factors for thromboembolic events include immobility, malignancy, pregnancy, surgery, and acquired or inherited thrombophilias, obesity, cigarette smoking, and hypertension. We present a case of a 59-year-old female who watched TV and developed leg swelling and was found to have PE and DVT.